A novel solventless coating method to graft low‐molecular weight polyethyleneimine on silica fine powders. Issue 19 (15th July 2014) - Murillo‐Cremaes, Nerea; López‐Aranguren, Pedro; Vega, Lourdes F.; Saurina, Javier; Roig, Anna; Domingo, Concepción
ABSTRACT The overall objective of the present study was to modulate the surface characteristics of aerogel‐like submicron and nanometric particles by coating them with polyethyleneimine (PEI) to suit specific biological applications. A new process for the covalent grafting of low‐molecular weight PEI chains has been described, based on the use of compressed CO2 as the initiator of the ring opening polymerization of the ethyleneimine monomer, which was performed in the presence of silica particles. Coating was done at low pressure and temperature and in the absence of any organic solvent. Obtained materials were compared with a product prepared following the standard soaking procedure for PEI coating. Materials were characterized regarding composition, structure, surface charge, particle size, morphology, and drug release. The developed process led to the covalent grafting of low‐molecular weight PEI on the silica surface, which conferred an increased thermal stability for the coating and low cytotoxicity to the particles. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 2760–2768